Occurrence of bisphenol A in wastewater and wastewater sludge of CUQ treatment plant - Dipti Prakash Mohapatra; Satinder Kaur Brar; Rajeshwar Dayal Tyagi; Rao Y. Surampalli (MDPI AG, 2011)
The identification and quantification of bisphenol A (BPA) in wastewater (WW) and wastewater sludge (WWS) is of major interest to assess the endocrine activity of treated effluent discharged into the environment. BPA is manufactured in high quantities fro its use in adhesives, powder paints, thermal paper and paper coatings among others. Due to the daily use of these products, high concentration of BPA was observed in WW and WWS. BPA was measured in samples from Urban Community of Quebec wastewater treatment plant located in Quebec (Canada) using LC-MS/MS method. The results showed that BPA was present in significant quantities (0.07 μg L–1 to 1.68 μg L–1 in wastewater and 0.104 μg g–1 to 0.312 μg g–1 in wastewater sludge) in the wastewater treatment plant (WWTP). The treatment plant is efficient (76 %) in removal of pollutant from process stream, however, environmentally significant concentrations of 0.41 μg L–1 were still present in the treated effluent. Rheological study established the partitioning of BPA within the treatment plant. This serves as the base to judge the portion of the process stream requiring more treatment for degradation of BPA and also in selection of different treatment methods. Higher BPA concentration was observed in primary and secondary sludge solids (0.36 and 0.24 μg g–1, respectively) as compared to their liquid counterpart (0.27 and 0.15 μg L–1, respectively) separated by centrifugation. Thus, BPA was present in significant concentrations in the WWTP and mostly partitioned in the solid fraction of sludge (Partition coefficient (Kd) for primary, secondary and mixed sludge was 0.013, 0.015 and 0.012, respectively).